Diagnostic difficulties in lesions of the minor salivary glands - Khurram, Syed A.; Barrett, A William; Speight, Paul M. (Diagnostic histopathology (Oxford, England : 2008), 2017)
A wide range of lesions arise from the intra-oral salivary glands, and often present a diagnostic challenge to specialists and generalists alike. Of the salivary neoplasms, pleomorphic adenoma is the most common, but its morphological diversity may bring several other entities to mind, notably polymorphous adenocarcinoma, particularly in a small incisional biopsy. Polymorphous adenocarcinoma in turn shares features with adenoid cystic carcinoma. Immunohistochemistry and molecular cytogenetic studies can assist diagnosis in the face of overlapping morphology. The other salivary neoplasms most likely to be encountered in the oral cavity are canalicular adenoma, mucoepidermoid carcinoma, secretory carcinoma and acinic cell carcinoma. Of the non-neoplastic conditions, necrotising sialometaplasia is most likely to be misdiagnosed as neoplastic on both clinical and histological grounds. However, careful consideration of the clinicopathological features of an adequate tissue specimen will enable correct diagnosis.